2009
DOI: 10.1002/cbic.200900183
|View full text |Cite
|
Sign up to set email alerts
|

Aphrodisiac Pheromones from the Wings of the Small Cabbage White and Large Cabbage White Butterflies, Pieris rapae and Pieris brassicae

Abstract: The small and large cabbage butterflies, Pieris rapae and P. brassicae, are found worldwide and are of considerable economic importance. The composition of the male scent-producing organs present on the wings was investigated. More than 120 components were identified, but only a small portion proved to be male specific. Major components were the known beetle pheromone ferrulactone (1) in P. rapae and its previously unknown larger analogue, brassicalactone (2), in P. brassicae. The latter carries an additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
80
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 52 publications
3
80
0
1
Order By: Relevance
“…In the genus Pieris, the male sex pheromone is known for both Pieris brassicae, P. rapae (Yildizhan et al, 2009), and P. napi (Andersson et al, 2007). The green-veined white butterfly, P. napi, is a well-documented model organism for evolutionary studies, and is one of the few butterfly species (see Nieberding et al, 2008) where both behavioral (e.g., and chemical (Andersson et al, 2000(Andersson et al, , 2007 background information is available on male sex pheromones.…”
Section: Introductionmentioning
confidence: 99%
“…In the genus Pieris, the male sex pheromone is known for both Pieris brassicae, P. rapae (Yildizhan et al, 2009), and P. napi (Andersson et al, 2007). The green-veined white butterfly, P. napi, is a well-documented model organism for evolutionary studies, and is one of the few butterfly species (see Nieberding et al, 2008) where both behavioral (e.g., and chemical (Andersson et al, 2000(Andersson et al, , 2007 background information is available on male sex pheromones.…”
Section: Introductionmentioning
confidence: 99%
“…A retroaldol-fragmentation of the hydroxycarbonyl compounds 6 or 7 follows that releases hexahydrofarnesylacetone and acetaldehyde or acetate. The intermediate 4 can be found as a trace component in the male wing extracts (Yildizhan et al, 2009). Alternatively, a direct oxidative cleavage of the double bond of 1 is possible, but the dioxygenase enzymes capable of doing this usually act on aromatic systems.…”
Section: Discussionmentioning
confidence: 99%
“…These authors also established the absolute configuration of insect-derived 1 for the first time. We have found that Pieris butterflies use 1 as a component of the aphrodisiac pheromone of the males (Yildizhan et al, 2009). Hexahydrofarnesylacetone is a known degradation product of (E)-phytol (3), a diterpene alcohol that occurs as a side chain of chlorophyll a in all plants.…”
Section: Introductionmentioning
confidence: 99%
“…In other Galleriinae, males often use TMPD-ol for communication: this compound is a component of the male sex pheromone of the African sugarcane borer Eldana saccharina (Burger et al, 1985(Burger et al, , 1993 and Tirathaba mundella (Sasaerila et al 2003) (Lepidoptera: Pyralidae: Galleriinae). TMPD-ol is also part of the maleproduced aphrodisiac pheromone of the small and large cabbage white butterflies Pieris rapae and Pieris brasicae (Yildizhan et al 2009), and the African butterfly, Bicyclus anynana (Nieberding et al, 2008). E-Phytol [(E)-3,7,11,15-tetramethyl-2-hexadecen-l-ol], a compound related to TMPDol, a constituent in the male-produced wing gland sex pheromone in a related species, Ephestia elutella (Lepidoptera: Pyralidae; Phycitinae; Phelan et al, 1986).…”
Section: Discussionmentioning
confidence: 99%